2016
DOI: 10.2169/internalmedicine.55.5756
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between Warfarin and Linezolid in Patients with Left Ventricular Assist System in Japan

Abstract: These findings suggest that co-administration of linezolid results in increased PT-INR in patients with LVAS treated with warfarin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 24 publications
(25 reference statements)
0
2
0
Order By: Relevance
“…DAP is also used to treat various bacterial infections caused by Gram-positive bacteria, including methicillin-resistant S. aureus (MRSA) and vancomycin-resistant Enterococci (VRE) [16,17]. As mentioned above, LZD and DAP are also known to interact with WF, and therefore, pharmacists monitor the fluctuation of PT-INR carefully and provide prescription support [18].…”
Section: Antimicrobial Agentsmentioning
confidence: 99%
“…DAP is also used to treat various bacterial infections caused by Gram-positive bacteria, including methicillin-resistant S. aureus (MRSA) and vancomycin-resistant Enterococci (VRE) [16,17]. As mentioned above, LZD and DAP are also known to interact with WF, and therefore, pharmacists monitor the fluctuation of PT-INR carefully and provide prescription support [18].…”
Section: Antimicrobial Agentsmentioning
confidence: 99%
“…It is commonly used to treat pneumonia and skin and soft tissue infections caused by some gram‐positive bacteria, including methicillin‐resistant Staphylococcus aureus (MRSA) and vancomycin‐resistant enterococci (VRE). 5 , 6 Although LZD often shows good safety in clinical therapy, 7 the related adverse effects are frequent and occasionally severe. 8 A previous study showed that the risk of adverse effects increased with LZD exposure and duration of treatment, 5 and physicians should be more cautious when prescribing antimicrobials such as LZD due to the risk of drug–drug interactions (DDIs).…”
Section: Introductionmentioning
confidence: 99%